Hudson bay : or, Everyday life in the wilds of North America, during six years' residence in the territories of the hon. Hudson bay company - Ballantyne, R. M. (Robert Michael), 1825-1894. (London, 1876)
First edition, Edinburgh, 1848. Added t.-p., with vignette. Mode of access: Internet.